Analysis of Subdistrict Governance for Equitable Public Services to Vulnerable Groups: A Case Study of North Banjarmasin Subdistrict Office - Hakim, Muhammad Lukman Nul; Kristanto, Budi (Program Pascasarjana Universitas Negeri Makassar, 2025)
Public service at the sub-district level serves as the frontline of government in ensuring citizens’ basic rights, particularly for vulnerable groups such as persons with disabilities, the elderly, and underprivileged families. This study analyzes governance practices in Banjarmasin Utara Sub-district by focusing on policy integration, staff capacity, collaboration among actors, and local cultural dynamics. A qualitative case study was conducted through in-depth interviews, participatory observation, and document review. The findings indicate that although regulations and standard operating procedures for priority services exist, their implementation is constrained by limited budgets, insufficient staff training, and uneven digital infrastructure. Community support, staff improvisation, and informal social networks help bridge institutional gaps, but may also lead to inequities. A hybrid model combining digital and face-to-face services emerges as an adaptive strategy to reach vulnerable groups. The study contributes by showing that the effectiveness of inclusive governance at the sub-district level depends on the synergy between formal policy, operational capacity, collaboration, and cultural sensitivity.